Implementation Silent Reading for English Subject at Islamic Education Department at STIT Aqidah Usymuni Sumenep: English - Moh. Zainol Kamal; Edyanto; Khairun Nisa'; Uswatul Jannah; Lailatul Jamila (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Silent reading refers to the act of reading without vocalizing the words. With this in mind, the researcher aimed to explore students' silent reading comprehension. This study adopted a qualitative research approach. Qualitative research, involves the systematic collection of data to uncover underlying patterns or meanings using scientific methods, typically pursued by researchers interested in understanding the nature of a phenomenon. This research used students of the Islamic Education Department at STIT Aqidah Usymuni Sumenep as objects. The conclusion showed that silent reading can also inspire students to share diverse ideas while reading silently. Students can acquire more information when they read in a quiet environment. When the conditions allow students to read comfortably, their concentration improves, and they can easily grasp the key points of the English text.